Effects of Conjugation of Ferrocene and Gallic Acid On desCys11/Lys12/Lys13-(p-BthTX-I)2K Peptide: Structure, Permeabilization and Antibacterial Activity - Pereira, Marina Rodrigues [UNESP]; Rodrigues, Vanessa Dos Santos [UNESP]; de Oliveira, Warlley Campos [UNESP]; Duque, Cristiane [UNESP]; da Silva, Benise Ferreira; Santos-Filho, Norival Alves [UNESP]; Carneiro, Victor Alves; Lorenzón, Esteban Nicolás; Cilli, Eduardo Maffud [UNESP] (Bentham Science Publishers, 2023)
Background: Antimicrobial resistance is an emerging global health challenge that has led researchers to study alternatives to conventional antibiotics. A promising alternative is antimi-crobial peptides (AMPs), produced as the first line of defense by almost all living organisms. To improve its biological activity, the conjugation of AMPs is a promising approach. Objective: In this study, we evaluated the N-terminal conjugation of p-Bt (a peptide derived from Bothrops Jararacuçu`s venom) with ferrocene (Fc) and gallic acid (GA). Acetylated and linear ver-sions of p-Bt were also synthesized to evaluate the importance of N-terminal charge and dimeric structure. Methods: The compounds were obtained using solid-phase peptide synthesis. Circular dichroism, vesicle permeabilization, antimicrobial activity, and cytotoxicity studies were conducted. Results: No increase in antibacterial activity against Escherichia coli was observed by adding ei-ther Fc or GA to p-Bt. However, Fc-p-Bt and GA-p-Bt exhibited improved activity against Staphy-lococcus aureus. No cytotoxicity upon fibroblast was observed for GA-p-Bt. On the other hand, conjugation with Fc increased cytotoxicity. This toxicity may be related to the membrane permeabi-lization capacity of this bioconjugate, which showed the highest carboxyfluorescein leakage in vesicle permeabilization experiments. Conclusion: Considering these observations, our findings highlight the importance of adding bioac-tive organic compounds in the N-terminal position as a tool to modulate the activity of AMPs.
Keywords: AMPs; Antibiotics; antimicrobial peptides; bioconjugate; S. aureus; vesicle permeabilization